What is the tryptophan kynurenine pathway and why is it important to neurotherapeutics?. (July 2015) - Davis, Ian; Liu, Aimin
<x xml:space="preserve">Abstract</x> The kynurenine pathway has received increasing attention as its connection to inflammation, the immune system and neurological conditions has become more apparent. It is the primary route for tryptophan catabolism in the liver and the starting point for the synthesis of nicotinamide adenine dinucleotide in mammals. Dysregulation or overactivation of this pathway can lead to immune system activation and accumulation of potentially neurotoxic compounds. These aspects make the kynurenine pathway a promising target for therapeutic development to treat inflammation and disease with neurological aspects, especially in cancer patients undergoing chemotherapy.